Comparison of Conventional and Advanced Concrete Technologies in terms of Construction Efficiency - Matej Špak; Mária Kozlovská; Zuzana Struková; Renáta Bašková (Advances in Materials Science and Engineering)
Nowadays, high-performance concrete (HPC) and ultra-high-performance concrete (UHPC) are ranked among advanced concrete technologies. The application of the mentioned advanced technologies may have potential to improve the construction efficiency from several points of view. For instance, reducing of construction time and construction material, construction quality improving, environmental impact minimizing, and increasing of both durability and lifetime of structures as well as reducing of total construction costs may be obtained. Particular advanced concrete technologies are described and the possibilities of their utilization in both monolithic structures and precast units are presented in the article. The main benefits of modern methods of construction (MMC) based on advanced concrete technologies application in precast elements production are presented. Regarding the selected aspects of construction efficiency assessment, a comparison of conventional and advanced concrete technologies that are applied in monolithic structures and precast units is made. The results of this comparison, estimated in semantic differential scale, are presented in the article. By the results of the comparison, the significance of applying the advanced concrete technologies in modern methods of concrete structures production is demonstrated in order to improve construction efficiency.